Clinical and imaging findings, treatments, and outcomes in 27 dogs with imaging diagnosed trigeminal nerve sheath tumors: A multi‐center study. Issue 6 (31st July 2017) - Swift, Katie E.; McGrath, Stephanie; Nolan, Michael W.; Young, Martin; Reese, Michael; Rao, Sangeeta; Randall, Elissa; Leary, Del; LaRue, Susan
Abstract: The clinical behavior of canine trigeminal nerve sheath tumors and benefits of previously reported treatments are incompletely defined. Aims of this retrospective, multicenter, observational study were to describe clinical signs, tumor localization characteristics, treatments, and clinical outcomes in a group of dogs with this neoplasm. Databases at four hospitals were reviewed for dogs with a trigeminal nerve sheath tumor diagnosis, magnetic resonance imaging (MRI) studies, and presentation between 2004 and 2014. A single observer recorded medical record findings and two observers recorded MRI characteristics by consensus. A total of 27 dogs met inclusion criteria (15 treated with stereotactic radiation therapy and 12 unirradiated). Two unirradiated dogs were excluded from outcome analyses. The most common presenting signs were masticatory muscle atrophy (26 dogs), neurologic signs referable to intracranial disease (13), and ocular disease (12). Based on MRI findings, all dogs had disease extending centrally at the level of the brainstem. The most commonly affected trigeminal nerve branches were the mandibular (26 dogs), maxillary (22), and ophthalmic (10). Of 15 dogs treated with stereotactic radiation therapy, one had improved muscle atrophy, and six had poor ocular health after treatment. Neurologic signs improved in 4/5 dogs with intracranial signs. Overall median survival time for the 10 unirradiated dogs with available follow‐up was 12 days and 441 days for the 15 stereotactic radiation therapy dogs. Mean survival times between these groups were not significantly different (mean 95% CI for unirradiated dogs was 44–424 days and mean 95% CI for stereotactic radiation therapy dogs was 260–518 days).